1994
DOI: 10.4012/dmj.13.131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Filler Content on Bonding Efficacy of 4-META MMA/TBB Bonding Agent

Abstract: The effect of adding micro filler to 4-META MMA/TBB dentin bonding agent was examined by measuring the wall-to-wall polymerization contraction gap of a commercial light-cured resin composite in a cylindrical dentin cavity and the tensile bond strength of the flat dentin surface. Gap formation was not completely prevented by using a filled dentin bonding agent although the tensile bond strength was significantly greater than that obtained using the unfilled dentin bonding agent. These results indicate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Several studies have reported that adhesives containing filler particles may be one of the important factors influencing dentin bond strength [24][25][26][27][28] . Miyazaki et al clearly indicated that the highest bond strength was obtained with 10 wt% filler level and that the bond strength gradually decreased with increasing filler content 28) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that adhesives containing filler particles may be one of the important factors influencing dentin bond strength [24][25][26][27][28] . Miyazaki et al clearly indicated that the highest bond strength was obtained with 10 wt% filler level and that the bond strength gradually decreased with increasing filler content 28) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have reported that the filler content in adhesive influenced the dentin bond strength of composite resin [24][25][26][27][28] . The experimental adhesive containing S-PRG filler for direct pulpcapping ideally possess both high efficacy of promoting a reparative dentin and high dentin bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, one factor influencing the marginal seal of composite resin restorations relies on the effectiveness and properties of the adhesive layer [6]. In order to improve the radiopacity, mechanical properties and durability, manufacturers have added filler particles to the adhesive composition [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some other bond strength studies, microtensile [24] and inverted cone tensile bond strength [25], reported no difference between filled and unfilled adhesives, meanwhile, Kasraei et al [9] reported an increase in microtensile bond strength with an incorporation of nanofiller of up to 1%. One study conducted by Tani et al [6] found that adding filler particles increased the tensile bond strength, but compromised the marginal seal compared to unfilled adhesive. One study from Martins et al [26] concluded that adding barium-borosilicate glass filler of up to 50% appeared to decrease the adhesive solubility without compromising its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…De uma forma semelhante ao que é feito com as resinas compostas, as partículas inorgânicas tendem a resultar num aumento da resistência coesiva da película de adesivo depositada sobre o substrato, a qual ajudaria a transmitir melhor as forças que incidem sobre a interface. Alguns autores tem constatado um aumento na resistência adesiva quando da adição de carga nos sistemas adesivos, assim como a diminuição da microinfiltração marginal (Tani et al, 1994;Perdigão et al, 1999). O adesivo também se torna mais viscoso, com a adição de partículas de carga, o que proporciona interfaces mais espessas e, consequentemente, mais elásticas que absorvem melhor o estresse da contração de polimerização das resinas compostas, evitando o descolamento da interface.…”
Section: Sistemas Adesivos E Interface Adesivaunclassified